2021
DOI: 10.3390/ijerph18020608
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamic Spatio-Temporal Correlations between PM2.5 Emissions from Different Sources and Urban Expansion in Beijing-Tianjin-Hebei Region

Abstract: Due to rapid urbanization globally more people live in urban areas and, simultaneously, more people are exposed to the threat of environmental pollution. Taking PM2.5 emission data as the intermediate link to explore the correlation between corresponding sectors behind various PM2.5 emission sources and urban expansion in the process of urbanization, and formulating effective policies, have become major issues. In this paper, based on long temporal coverage and high-quality nighttime light data seen from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Meanwhile, Wuhai's environmental governance and urban transformation management methods have been linked to a decline in particulate matter concentration in recent years. Further, it is compatible with the current state of pollution in the Beijing-Tianjin-Hebei region and nearby cities (Zhao and Xu, 2021). As noted previously, enhancing pollution management methods is critical for reducing public health damage.…”
Section: Discussionmentioning
confidence: 57%
“…Meanwhile, Wuhai's environmental governance and urban transformation management methods have been linked to a decline in particulate matter concentration in recent years. Further, it is compatible with the current state of pollution in the Beijing-Tianjin-Hebei region and nearby cities (Zhao and Xu, 2021). As noted previously, enhancing pollution management methods is critical for reducing public health damage.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, urban management of subprovincial cities and municipalities directly under the central government has certain distinct features. Therefore, we deleted all the provincial capital cities, sub-provincial cities, and municipalities, and re-regressed the model (1). Column (2) of Table 4 reports these results.…”
Section: Excluding the Impact Of Administration Hierarchymentioning
confidence: 99%
“…(1) Urbanization has exacerbated environmental pollution. Zhao and Xu [1] believe that transportation, industry, and energy production may have negative effects on the environment in the process of urbanization. Wang et al [2] found that urbanization not only increases haze concentrations in the region, but it also has a spillover effect on neighbouring areas.…”
Section: Introductionmentioning
confidence: 99%
“…Their research uses various climate indicators such as temperature (Xu et al 2021), soil conditions (Sachdeva et al 2018), precipitation (Brogan et al 2019), wind (Daşdemir et al 2021), El Nino-Southern Oscillation (Cardil et al 2021), and others. The methods used also vary, ranging from regression (Zhao and Xu 2021), classification (Sulova and Arsanjani 2021), clustering (Viana-Soto et al 2020), neural networks (Larsen et al 2021), to copula (Xi et al 2020).…”
Section: Introductionmentioning
confidence: 99%